Natural occurrence of deoxynivalenol and zearalenone in wheat from Jiangsu province, China - Ji, Fang; Xu, Jianhong; Liu, Xin; Yin, Xianchao; Shi, Jianrong (Food chemistry, 2014)
•A three-year survey was conducted to evaluate the natural occurrence of DON and ZEN in FHB frequently epidemic region.•74.4% Wheat samples were DON contaminated, while 12.8% of them were ZEN contaminated.•Rainfall from flowering to harvesting plays a major role in DON and ZEN accumulation. A three-year (2010–2012) survey was conducted to assess the prevalence and concentrations of deoxynivalenol (DON) and zearalenone (ZEN) in wheat from several regions of Jiangsu province, China, which are heavily impacted by Fusarium head blight. A total of 180 wheat samples were obtained from the infected fields that spread 21 counties. DON and ZEN levels were determined by liquid chromatography–mass spectrometry (LC–MS/MS). DON was found in 74.4% of samples at levels ranging from 14.52 to 41157.13μg/kg (mean 488.02μg/kg), while ZEN was found in 12.8% of samples at levels ranging from 10.13 to 3048.88μg/kg (mean 73.04μg/kg). In years and regions of higher rainfall, DON and ZEN levels were higher in samples. These results are necessary to take a vigilant attitude to prevent human intake of trichothecenes and protect human’s health from the risk of exposure to these toxins.